THE ROLE OF THE COURTS IN PROVIDING LEGAL AID SERVICES TO THE POOR BASED ON LAW NUMBER 16 OF 2011 ABOUT LEGAL AID - Dewa Sujira; Muhammad Arif Sahlepi (Universitas Efarina, 2023)
The implementation of the Legal Aid Post (Posbakum) by the District Court includes 3 (three) scopes of legal services in accordance with the provisions contained in Perma No. 1 of 2014. These 3 things are the service of waiving case fees, and holding trials outside the court building as well as Providing Court Posbakum. In relation to the implementation of Posbakum, the District Court only provides Posbakum room facilities for three accredited Legal Aid Providers or advocate organizations. Meanwhile, regarding legal aid funds for handling each case, it will be submitted by the Court through the Regional Office of the Ministry of Law and Human Rights. However, this does not mean that the function of this facilitator can be simply ignored, considering that the Posbakum is housed in the Court, it is worth noting that there is a special mandate from the State Administrators to the Court to be able to make legal services successful free of charge for the poor, of course. In this way, it can also be hoped that the presence of Posbakun in the Court environment will be able to erode the negative and frightening stigma about the Court for the general public.